Determinants of hand hygiene compliance among healthcare workers in intensive care units: a qualitative study - Salah Alshagrawi; Norah Alhodaithy (BMC, 2024)
Abstract Background Practicing hand hygiene is a cost-effective method to decrease the occurrence of Healthcare-Associated Infections (HAIs). However, despite their simplicity, adhering to hand hygiene methods among healthcare workers (HCWs) can be highly challenging. We aim to examine the factors influencing hand hygiene compliance as perceived by HCWs working in the intensive care units (ICUs) at several major hospitals in Riyadh, Saudi Arabia. Method This qualitative study was conducted by adopting a content analysis to examine the interviews of HCWs who are currently working in the ICUs of various major hospitals located in the capital city of Riyadh, Saudi Arabia. Results We interviewed 49 HCWs working in ICUs, with an average age of 38 and 8 years of experience. The HCWs comprised doctors (n = 12), anesthesiologists (n = 6), and nurses (n = 31). There were 34 females and 15 males among the participants. Our analysis revealed several factors that impact hand hygiene compliance, including individual, work/environment, team, task, patient, organizational, and management concerns. Several obstacles and possibilities for enhancement have been identified. Conclusion The results of this study would enhance our comprehension of hand hygiene practices and serve as a foundation for creating future strategies and assessment methods to enhance compliance with hand hygiene protocols in ICUs.